Analyse des retombées intermédiaires d’un dispositif de développement professionnel sur le soutien du développement langagier en centre de la petite enfance - Bergeron-Morin, Lisandre; Hamel, Christine; Bouchard, Caroline (Canadian Journal of Education/Revue canadienne de l'éducation, 2021)
This study documents the implementation of a professional development initiative to support language development for children in early childhood centres. The initiative, which includes a co-intervention modality with a speech-language pathologist, was offered to four educators. Using a mixed design and the Coldwell and Simkins (2011) logic model, the intermediate outcomes of the system are analyzed, namely the educators’ reactions, the new knowledge they acquired and the skills they developed, as well as the changes in their practices to support language development. A triangulation between data on the frequency of use of fifteen language development support practices and the analysis of interviews with educators underlines the importance of anchoring this new knowledge and skills in educators’ daily lives and provides a better understanding of certain challenges inherent to changes in practices. Keywords: early childhood education and care, professional development, language development supporting practices, logic model, interprofessional collaboration